2012
DOI: 10.1177/147323001204000117
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in the Clinical Outcome of Patients with Multiple Blunt Trauma

Abstract: OBJECTIVE: This prospective study evaluated serum total oxidant status (TOS), total antioxidant status (TAS) and oxidative stress index (OSI), along with the Revised Trauma Score (RTS) and Injury Severity Score (ISS), as predictors of clinical outcome in the early posttraumatic period in patients with multiple blunt trauma (MBT). METHODS: The study included 52 patients admitted to the emergency department with MBT and 40 age-and sex-matched healthy control subjects. RESULTS: The overall MBT patient mortality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The significant contribution of non-TBI trauma to the decline in serum free thiol concentrations of the TBI group is unsurprising. Various studies have demonstrated an important role of oxidative stress in trauma such as in multiple blunt trauma and abdominal trauma [ 34 , 35 ]. A mechanism by which oxidative stress occurs after non-TBI trauma is through activation of neutrophils which can generate free radicals in a process called the ‘oxidative burst’ [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significant contribution of non-TBI trauma to the decline in serum free thiol concentrations of the TBI group is unsurprising. Various studies have demonstrated an important role of oxidative stress in trauma such as in multiple blunt trauma and abdominal trauma [ 34 , 35 ]. A mechanism by which oxidative stress occurs after non-TBI trauma is through activation of neutrophils which can generate free radicals in a process called the ‘oxidative burst’ [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been evaluated in people in many different diseases including asthma, active and passive smoking, heart failure, renal failure, cancer, COPD, pulmonary hypertension, diabetes mellitus, ischemia and reperfusion injury, periodontal disease, blunt trauma, pneumonia, and ARDS . In large animals, changes in various biomarkers indicative of oxidative stress has been documented in a wide variety of conditions including recurrent airway obstruction in horses and various inflammatory diseases in cows and horses …”
Section: Inflammatory Respiratory Diseasementioning
confidence: 99%